Modelagem e otimização simultânea de processos de medição e fabricação por filamento fundido - Barbosa, Francisco Tiago Araújo (2024)
Additive manufacturing using fused filament fabrication (FFF) is transforming the production of three-dimensional parts. However, the quality of printed parts can vary and may not meet customer specifications, raising questions about performance, precision, and the evaluation of the measurement system. Therefore, there is a need for research to address these issues related to the quality of 3D-printed products. This dissertation presents a set of studies on modeling and multi-response optimization for the additive manufacturing process. The main objective of this research is to propose an optimization method capable of adjusting the effects of printing parameters, such as layer width, layer height, infill density, and printing speed, on the responses of dimensional accuracy and measurement system precision. To achieve these goals, the following specific objectives were set: analyze the state-of-the-art in fused deposition modeling; simultaneously optimize the manufacturing process and the measurement system; improve operational performance, dimensional accuracy, and the measurement system; and optimize printing parameters with respect to energy consumption. A central composite design (CCD) experimental plan was used in conjunction with response surface methodology to assess the effects of factors on response variables. Quadratic regression models were estimated using the Ordinary Least Squares (OLS) method. For multi-objective optimization, the desirability method and the normalized global criterion (NGC) method were employed. The optimal configurations proposed by the desirability method were a layer width of 0.6 mm, a layer height of 0.28 mm, an infill density of 90%, and a speed of 50 mm/s. The expected results are: dimensional accuracy (Y̅w = 10.00, Y̅t = 4.02, Ca;w = 1.00, Ca;t = 0.99) and measurement system precision (Cgk;w = 2.387 and Cgk;t = 1.846). In the second proposal, parameters were added to the dimensional precision responses (E and Ct). After optimization using the normalized global criterion (NGC) method, the results were: LW = 0.59, LH = 0.12, ID = 10.00, and S = 50.00. Thus, this research aims to enhance fused filament fabrication by providing practical solutions to improve the quality and efficiency of three-dimensional part production